PERSEPSI ORANGTUA TERHADAP KONTEN YOUTUBE KIDS SEBAGAI STIMULASI PENAMBAHAN KOSAKATA ANAK - Nurur Rohmah Hidayati; Siti Fadjryana Fitroh (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2023)
Parents' Perceptions of Content Youtube kids as a Stimulation for Children's Vocabulary Addition. The method used in this research is descriptive-quantitative research method. The steps of the method were research and data collection, data reduction, data display, conclusion drawing and verification. Based on the data collected, qualitative data was converted into quantitative data so that descriptive data analysis was used. The data obtained from the research is processed by means of questionnaire analysis, and observation analysis. The techniques of data collection were using questionnaire (parents’ perception questionnaire), observation of content Youtbe kids’ influences in providing stimulation of children’s vocabulary addition, and documentation. The results of the research showed that the value obtained by the grand mean 3.48805 on the sub variable of parents' responses, 3.0088 While in the sub variable of parents' opinions. And 2.9107 on the sub variable of parents' assessment. While the observation results obtained a grand mean of 2.23 on observing children's ability to pronounce vocabulary. and 2.45 while the observation of the children's ability to recognize the vocabulary seen in the video in content youtube kids. Based on the results of the research that has been done, it can be concluded that the Parents' Perception of content Youtube kids as a Stimulation of Children's Vocabulary Addition is very positive.